We're all in this together . . . : so make some room - Papa, Tom (St. Martin's Press, 2023)
"Stand-up is all well and good, but observational humor that's funny and warm may work best in books. And Tom Papa, whose loyal audiences are packed with "date night" couples of all ages, has perfected the form. In We're All In This Together, Papa's thirty-seven short essays tackle these universal American topics, among others: -Love for Your First Car ("To Buy or Lease") -The Truth about Personal Hygiene ("How You Know When It's Time to Go") -Date Nights ("Will You Go Out with Me?") -Unfamiliar Hotel Rooms ("Why Nothing Works") -Pets ("Cats--Ancient Menace") -Drinking ("There's no Cure for a Hangover") -Ducking your Family, even Though you Love Them ("The Lesson of Mark Twain's Cigars") Tom Papa's books make readers laugh, but--crucially--feel better about themselves while doing it. And while there's thematic overlap with Papa's stand-up, with a couple of exceptions, all the writing here is fresh for our book"--